Aging and the self : perceptions of the aging process and one's body on the development of the self among Singaporean seniors - Khrisha Chatterji (2014)
This research analyzes the perceptions of the aging process and one’s body on the development of the self among Singaporean seniors. Interviews with sixteen seniors were conducted to gain insight into what the aging process is like from their perspectives and how they viewed their bodies as they age. These seniors see aging as an experience that is shaped by biological, chronological, psychological and social processes. Gender also plays a huge role in the shaping of differentiated experiences of aging among male and female seniors. These views affect the way one sees one’s self. The analyses show that the aging body is seen in contrast to the youthful body which is deemed ideal. Unlike their Western counterparts, findings suggest that Singaporean seniors tend to be accepting of the aging process and are willing to deal with the changes that come with aging.